FACTORS THAT INFLUENCE MENDONG FARMERS’ INCOME - Suyudi; Rudi Priyadi; Rina Nuryati; Zulfikar Noormansyah (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
. Mendong (Fimbristylis umbellaris) is a plantation commodity used as a raw material in the creative industry. However, farmers engaged in mendong cultivation face challenges such as declining market demand and increasing production costs, forcing them to sell their products at lower prices. This study aims to analyze the average production, production costs, selling prices, and income of mendong farmers, as well as to examine the simultaneous and partial effects of production, production costs, and selling prices on farmer income. The research employed a survey method. The sample comprised 50 percent of the total population of 68 mendong farmers, selected using simple random sampling. The study was conducted in Kamulyan Village, Manonjaya District, Tasikmalaya Regency. Data were collected through structured questionnaires and direct interviews with respondents. Analytical methods included cost, revenue, and income analysis, along with multiple linear regression to assess the factors influencing farmer income. Results indicated that the average mendong production was 104.381 quintals per hectare, with average production costs of IDR 27,444,502 per hectare, an average selling price of IDR 576,471 per quintal, and an average income of IDR 32,187,576 per hectare in the third production cycle. Simultaneously, production volume, production costs, and selling prices significantly influenced farmers’ income. Partially, production volume and selling prices had a positive effect, while production costs had a negative effect on income.